Nursing Education During COVID-19 Pandemic: Way Forward for Teaching Hospitals in Nepal - Singh, Babita (Europasian Journal of Medical Sciences, 2020)
COVID-19 pandemic has affected nursing education globally, with more impact in nations like Nepal with limited resources. Although, the use of technology and virtual platforms has long history in nursing education, it is relatively very new for teaching hospitals in Nepal where the health system is fragile. The challenges seen in nursing education have depicted an urgent need to address nation’s gaps in educational infrastructure including capacity building of faculties and enabling nursing students to utilize technology effectively. In fact, the pandemic has unveiled underlying structural vulnerabilities and existing disparities in educational settings between nations, particularly in nursing education.